Faktor Yang Memengaruhi Perilaku Cuci Tangan Pakai Sabun Siswa/I Di Masa Pandemi Covid 19 Di Madrasah Ibtidaiyah Negeri 3 Kecamatan Kuta Blang Kabupaten Bireuen - Hilma Muzni; Ismail Efendi; Endang Maryanti (LPPM STIKES Siti Hajar dan Insight Power, 2023)
Abstract- Washing hands with soap is an effective way for preventive health efforts. This study aims to analyze the factors that influence the behavior of washing hands with soap in students during the Covid 19 pandemic at Madrasah Ibtidaiyah Negeri (MIN) 3 Bireuen, Kuta Blang District, Bireuen Regency. This research is a quantitative study with a cross-sectional study design that takes place from May to June 2022. The research sample is all school age children from grades III, IV and grades V totaling 70 people. The technique used is proportional stratified random sampling. The survey data were analyzed using Chi Square test and logistic regression. The results showed that there was an influence of knowledge on the behavior of washing hands with soap in students during the Covid 19 pandemi (p=0,009), there was an influence of the ease of getting a Washing hands with soap place on the behavior of washing hands with soap (p=0,000), there was an influence of the role of parents on the behavior of washing hands with soap (p=0,000), there was an influence of the role of parents on the behavior of washing hands with soap (p=0,000). teachers on the behavior of washing hands with soap (p=0,000), there was an influence of the role of school friends on the behavior of washing hands with soap for students during the Covid 19 pandemic at Madrasah Ibtidaiyah Negeri (MIN) 3 Bireuen, Kuta Blang District, Bireuen Regency (p=0,000). The conclusion in this study is that the five variables in this study have an influence on the behavior of washing hands with soap and the variables that affect the behavior of washing hands with soap in students during the Covid 19 pandemic at Madrasah Ibtidaiyah Negeri (MIN) 3 Bireuen, Kuta Blang District, Bireuen is the variable of the parent's role p value 0,001 with OR 7,382, CI 2,322-30,072. The suggestions in this study are for parents to always pay attention and supervise their children's behavior and provide information about the factors that influence hand washing behavior in school children. Keywords: Factors, Washing Hands with Soap, Covid 19